A PRMT5-RNF168-SMURF2 Axis Controls H2AX Proteostasis - Du, Changzheng (Cell Rep, 2019)
H2AX safeguards genomic stability in a dose-dependent manner; however, mechanisms governing its proteostasis are poorly understood. Here, we identify a PRMT5-RNF168-SMURF2 cascade that regulates H2AX proteostasis. We show that PRMT5 sustains the expression of RNF168, an E3 ubiquitin ligase essential for DNA damage response (DDR). Suppression of PRMT5 occurs in methylthioadenosine phosphorylase (MTAP)-deficient glioblastoma cells and attenuates the expression of RNF168, leading to destabilization of H2AX by E3 ubiquitin ligase SMURF2. RNF168 and SMURF2 serve as a stabilizer and destabilizer of H2AX, respectively, via their dynamic interactions with H2AX. In supporting an important role of this signaling cascade in regulating H2AX, MTAP-deficient glioblastoma cells display higher levels of DNA damage spontaneously or in response to genotoxic agents. These findings reveal a regulatory mechanism of H2AX proteostasis and define a signaling cascade that is essential to DDR and that is disrupted by the loss of a metabolic enzyme in tumor cells.